Penerapan Model Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Kelas IV MIN 25 Aceh Besar - Mahyana M (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This classroom action research aimed to improve the critical thinking skills of fourth-grade students at MIN 25 Aceh Besar through the implementation of the Problem Based Learning (PBL) model on the theme Always Saving Energy. The study employed a pre-experimental design using a One Group Pre-test Post-test Design and involved students from class IVA. Data were collected through a critical thinking skills test and a student response questionnaire. The critical thinking test consisted of essay questions covering five indicators: identifying problems and issues, predicting the consequences of an event, drawing conclusions, formulating simple hypotheses, and understanding relevant and irrelevant concepts. The results showed a significant improvement in students’ critical thinking skills after the implementation of the PBL model, with the initial category of Not Critical improving to the Critical category in the post-test. The t-test results confirmed that the improvement was statistically significant, indicating the effectiveness of PBL in enhancing critical thinking skills. The indicator of formulating simple hypotheses showed the highest improvement, reaching the Very Critical category, while the indicator of understanding relevant and irrelevant concepts showed the lowest improvement, remaining in the Fairly Critical category. In addition, students’ responses to the implementation of PBL were very positive, categorized as Very Good, indicating that this model created an enjoyable learning environment and motivated students to engage actively in learning. This study concludes that the Problem Based Learning model is effective in improving elementary school students’ critical thinking skills and receives very positive responses from students.